Effect of Horizontal Opening of Bottom Trawl on Fish Catch - K.K., Kunjipalu; N., Subramonia Pillai; M.R., Boopendranath; K., Krishna Rao (Fishery Technology, 2025)
Influence of horizontal opening on the catch of different species groups, in respect of three designs of bottom trawls have been evaluated through field trials. 25 m high opening trawl was found to be most effective for catdiing ribbon fish and small miscellaneous fish at a horizontal opening of 15-16 m. For Lactarius sp.and Sciaenids, 25 m large mesh trawl was found to bemost efficient and the horizontalopening of18-20 m and 16-18 m respectively were found to be optimum for the two species groups. For squid and cuttle fish, 25.6 m BOBP high opening trawl gave better performance at a horizontal opening of 16-17 m and beyond this range, its performance was similar to that of 25 m large mesh trawl.